Penerapan Teori Belajar Kolaboratif Luring dalam Pembelajaran Kelompok di SMA melalui Kajian Literatur - Arikah Putri Afriani; Innes Prameswary; Selestina Rebacca Sihotang; Tiara Alifia Azzahra; Eka Putri Azrai (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study evaluates the implementation of collaborative learning theory in high school education through a comprehensive literature review. Collaborative learning is an educational approach that encourages students to work together in groups to achieve shared learning objectives. The research aims to analyze the effectiveness of this approach in enhancing student learning outcomes, active participation, scientific attitudes, and critical thinking skills. The methodology involves the collection, selection, and analysis of relevant literature from various sources, including scientific journals, books, and research articles published between 2018 and 2023. The findings indicate that collaborative learning significantly improves students' academic performance and fosters a more interactive and dynamic learning environment. Additionally, it highlights the versatility of collaborative learning, demonstrating its applicability across various subjects, both in the sciences and humanities. The study concludes that implementing collaborative learning strategies can create a more engaging educational experience, promoting deeper understanding and motivation among students. This research underscores the importance of innovative teaching methods in enhancing educational quality and preparing students for future challenges. Overall, the study advocates for the integration of collaborative learning in high school curricula to optimize student learning experiences and outcomes.